Peran Sistem Informasi dalam Menciptakan Keunggulan Kompetitif Melalui Transformasi Teknologi - Johan Arifin (Universitas Islam Indonesia, 2005)
In a competitive market, many companies cannot avoid the competition. The right technology and information system can be the key factor in sustaining corporate viability. The information system changes the way of company in running its business and making some new things in the organization. Nowadays, the progress in information system followed by the pro¬gress in information technology. Therefore, information technology as a strategic business tool is essential to a firm, and central to its competitive strategy. This paper tries to discuss the aim of information system to create competitive advantage trough the use of tech¬nology transformation Keywords: Information system, Competitive advantage, Technology transformation.